Prevalence of Group A Beta Hemolytic Streptococcus Related Pharyngitis in Pakistan - Zafar Mahmood, Ikram Ullah, Sohail Tirmizi, Mohammad Yousuf, Zubair Anwar, Hammad Raza, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To identify the prevalence of group A beta hemolytic streptococcus related pharyngitis in Pakistan. Study Design: Retrospective Study Place and Duration of Study: Department of ENT and Head & Neck Surgery, Liaquat College of Medicine & Dentistry, Karachi from 1st July 2021 to 31st March 2022. Methodology: One hundred and seventy patients who showed symptoms of pharyngitis were enrolled. Two throat swabs were taken where first was used for rapid group a beta hemolytic streptococcus assessment. In cases of negative testing second swab was placed on 5% of the sheep blood agar plates at a temperature of 35°C with anaerobic conditions for two days. Beta hemolytic streptococcus colonies were checked. On sub-culturing pyrrolidonyl-arylamidase test was applied. A disc of >15mm with inhibited growth around bacitracin was considered as positive for group A β-hemolytic. Result: The present study found that the mean age of the patients was 19.5±4.3 years. There were 51.7% males while 48.2% females in this study. There were 11.17% those who were found positive for group a beta hemolytic streptococcus There was a significant association between rapid test positive and modified Centor scoring assuming that as score increases from 0-3 the risk of group a beta hemolytic streptococcus positive cases also surges. Conclusion: There is a significant prevalence of group A beta hemolytic streptococcus in pharyngitis cases reported from Pakistan. Keywords: Prevalence, Pharyngitis, Group A ß-hemolytic, Streptococcus